The Role of the Judiciary in the Interpretation of the Constitution of Pakistan - Raehah; Muhammad Huzaifa Bashir; Malik Abdullah; Nabeel Abbas; Mubassir Billah, (Dialogue Social Science Review (DSSR), 2025)
This research paper examines the crucial role of the judiciary, with a focus on the Lahore High Court, in the interpretation of the Constitution of Pakistan. Using a qualitative doctrinal legal research approach, the study assesses landmark judgments to uncover how the Court has influenced constitutional jurisprudence. The Lahore High Court has played a key role in protecting fundamental rights, illustrated by its recognition of maternity leave as a fundamental right and its annulment of colonial-era sedition laws. The Court's proactive efforts to advance gender equality are evident in its rulings on discriminatory age definitions in child marriage laws. Additionally, the Court has held the government accountable for environmental negligence, requiring the implementation of policies to address climate change. While the Court has shown judicial activism in some areas, it has also practiced restraint, recognizing the non-self-executing nature of the Objectives Resolution. The study highlights the Lahore High Court's dynamic balance between activism and restraint, which strengthens democratic governance and constitutional supremacy in Pakistan. Through its legal decisions, the Court not only tackles current legal issues but also establishes lasting precedents that foster the country's legal and democratic progression. This analysis affirms the judiciary's essential function in interpreting the Constitution to maintain the rule of law and safeguard individual freedoms.